Emotional understanding among university students - Prof. Dr. Aseel Abdul Kareem; Fatima Joory Hmaza (Journal of College of Education, 2023)
The current research aims at identifying Emotional understanding among university students, The current research community was determined by the students of Wasit University for morning studies for the academic year (2021-2022), who numbered (16528), with (8041) male and(8487) female , To achieve the objectives of the research, the scale of (Caruso & Mayer ,1998)  has been adopted for measuring Emotional understanding, after the researcher has ascertained the validity, reliability and validity of its translation of the scale, the research sample that consists of (400) male and female students from Wasit University. The sample is chosen by stratified random method from the research community where the results show , University students have Emotional understanding . In light of the results, the researcher developed a set of conclusions, recommendations and suggestions
Keywords: Emotional understanding, University students.